Lectotypification of the Linnaean name Lobelia coronopifolia (Campanulaceae) - Khan, Raees; Ul Abidin, Sheikh Zain; Mumtaz, Abdul Samad; Altinordu, Fahim; Sennikov, Alexander (Phytotaxa, 2017)
The genus Lobelia Linnaeus (1753: 929) honors the memory of Mathias de l’Obel (1538–1616), a Flemish physician and botanist who published important pre-Linnaean works on plant classification (see Shosteck 1974). Lobelia, a genus native to the New World, northern and western Europe, Africa, southern and eastern Asia, Australia and New Zealand, comprises 415 species and it is the second largest genus out of the 84 ones which currently belong to Campanulaceae Juss. (Lammers 2011).